(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the texts of school head’s welcome published by the school administration on the websites of British schools were analyzed from a cognitive point of view. In the analysis, 10 websites of the top 100 schools of Great Britain published on https://www.best-schools.co.uk in 2022 were selected. According to the results of the research, the speech of each school head has its own cognitive characteristics. The existence of such cognitive features serves to increase the interest and demand for school, if the speech texts directly affect the cognitive processes of the potential audience, that is parents or representatives, as well as students.